Does intramedullary elastic nail augmentation increase resistance to bending stress in plate fixation of long bones? A biomechanical study on lamb cadaveric femurs - Eren, Erdal; Buyukdogan, Halil; Erturk, Cemil; Turkcan, Julide Hazal; Kelesoglu, Ergun (TURKISH JOINT DISEASES FOUNDATION, 2023)
Objectives: The aim of this study was to evaluate the bending strength of plate-screw fixation augmented with titanium elastic nails (TENs) in a simple long bone fracture model using lamb cadaver femurs. Materials and methods: A total of 24 lamb cadaveric femurs that were osteotomized transversely from the mid-diaphysis with a bone saw were used to obtain a simple fracture model. The femurs were divided randomly into three groups. In Group 1, only plate-screw was used for fixation. In Group 2, plate-screw fixation was augmented with a 2.5-mm TEN. In Group 3, plate-screw fixation was augmented with two 2.5-mm TENs. Each bone model was positioned on a mechanical testing machine. Subsequently, three-point bending loads were applied to each bone to measure the force required for failure at the osteotomy site. The data were recorded on a computer connected to the test device and the bending strengths of all samples were calculated.Results: There was no statistically significant difference in the bending strength (megapascals) between Groups 1 and 2 or between Groups 2 and 3 (p>0.05). However, the bending strength in Group 3 was significantly higher than in Group 1 (p<0.05).Conclusion: The application of intramedullary TEN during surgery in long bone fractures, combined with a bridge plate, may be helpful to strengthen the fixation stability.
Keywords: Biomechanics; diaphyseal fractures; elastic nail augmentation; plate fixation; three-point bending; FEMORAL-SHAFT FRACTURES; INTERNAL-FIXATION; EXTERNAL FIXATION; TITANIUM NAILS; OSTEOSYNTHESIS; STABILITY; CHILDREN; Orthopedics; Surgery